Formulation of stomach-specific floating microparticles of nizatidine and their radiographic evaluation - Sajjan Singh Seema Rathore; Muniyappa Geetha; Basappa Palur Manjula; Vijaya Gopalachar Joshi; Siddamsetty Ramachandra Setty (Universidade de São Paulo, 2022)
Abstract Nizatidine is an anti-secretogogue and a gastroprotective drug with a half-life of 1-2 h and is well absorbed in the stomach. This study aimed to optimize the process and develop floating microparticles of nizatidine that are based on low methoxyl pectin. Oil-in-oil dispersion method and Taguchi orthogonal array design were employed, and the prolonged residence time of the microparticles in the stomach was demonstrated. The constraints for independent variables, viz. A-polymer, B-internal solvent volume, C-surfactant, D-stirring rate and E-stirring time were set to generate the experimental runs. Particle size, percentage yield, micromeritic properties, entrapment efficiency, in vitro buoyancy and in vitro release were characterized. Surface morphology, zeta potential, in vitro release kinetics and in vivo floating performance of the optimized formulation was examined. The microparticles were free-flowing, irregular in shape and had a mean particle size distribution of 73-187 μ. Low methoxyl pectin played a predominant role in achieving buoyancy and optimum gastric retention for the modified release of the drug, suggesting Korsmeyer-Peppas model as the possible release mechanism. In vivo radiographic study in rabbits revealed that the drug was retained in the stomach for a period of 6 h. These results indicate that nizatidine floating microparticulate system provides modified drug release for the effective treatment of gastric ulcer.